The Effectiveness of Gadget Protection Implementation in Purchasing Gadgets at Shopee Indonesia E-Commerce - Audina Rizka Zahra; Juliana Nasution (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
This research focuses on the success rate of implementing gadget protection in purchasing gadgets at Shopee Indonesia E-commerce. The purpose of this study is to find out how far the success rate is for implementing gadget protection when purchasing gadgets at Shopee Indonesia e-commerce. The method used in this research is using a descriptive qualitative method with a phenomenological approach. Where to understand the meaning based on the experience of facts that have been experienced by individuals in detail. The results of this study are that researchers took three informants, one informant was satisfied with the effectiveness of the implementation of the gadget protection provided by e-commerce Shopee Indonesia. However, the informant did not reach the claim stage, because the gadget he had purchased was still in good condition and nothing happened. Meanwhile, two other informants thought that the effectiveness of the implementation of this gadget protection was not working properly, they had difficulty making claims.